Siglec-9 acts as an immune checkpoint marker on MDSCs in brucella infection - Shi, Huidong; Qi, Xinxin; Shang, Kaiyu; Tian, Tingting; Ding, Jianbing; Li, Mingzhe; Xu, Ruixue; Pu, Fuling; Kuang, Junyu; Zhu, Yuejie; Zhang, Fengbo (Frontiers in Cellular and Infection Microbiology, 2025)
BackgroundBrucellosis is a zoonotic disease that is widely prevalent in the Xinjiang region of China. Once it progresses to a chronic stage, it can lead to significant complications. Immune checkpoints markers on Myeloid-derived suppressor cells (MDSCs) may lead to the chronic stage of the disease. This study analyzed the changes in MDSCs, immune checkpoints markers and cytokines in the patients with acute and chronic Brucella infections and after antibiotic treatment, to explore their roles and provide new ideas for future clinical treatment.MethodsA total of 37 patients with acute brucellosis infection (ABI) and 46 patients with chronic brucellosis infection (CBI) and 43 healthy controls (HC) subjects were enrolled. Flow cytometry was used to detect the expression of MDSCs, Siglec-9+MDSCs, PD-1+MDSCs and Tim-3+MDSCs before and after antibiotic treatment. In addition, ELISA was used to measure the levels of cytokines and the changes in IL-6 and Arg-1 of them were assessed again after antibiotic treatment.ResultsOur study found that the levels of MDSCs in the patients significantly increased, with CBI patients exhibiting higher levels than ABI patients. The cytokines showed varying degrees of elevation. Furthermore, after antibiotic treatment, the levels of MDSCs, Siglec-9+ MDSCs, PD-1+ MDSCs and Tim-3+ MDSCs in effective treatment patients significantly decreased. In contrast, the levels of MDSCs in ineffective treatment patients increased, while there were no significant differences in PD-1+ MDSCs and Tim-3+ MDSCs levels compared to before treatment. Notably, the levels of Siglec-9+MDSCs in ineffective treatment showed a significant increase. In the ineffective treatment patients, the serum levels of Arg-1 and IL-6 both increased compared to before treatment. Correlation analysis revealed a positive correlation in ineffective treatment patients between serum Arg-1 levels and MDSCs, as well as Siglec-9+ MDSCs levels, while no correlation was observed between IL-6 levels and immune cell parameters.ConclusionMDSCs are increased in both ABI and CBI. Siglec-9 acts as an immune checkpoint on MDSCs in patients with ineffective treatment responses. Therefore, Siglec-9 represents a potential prognostic marker for Brucella infection. Ongoing research on prognostic markers of brucellosis is promising, and further clinical studies are warranted to validate these findings.